Large-diameter trees dominate snag and surface biomass following reintroduced fire - Lutz, James A.; Struckman, Soren; Furniss, Tucker J.; Cansler, C. Alina; Germain, Sara J.; Yocom, Larissa L.; McAvoy, Darren J.; Kolden, Crystal A.; Smith, Alistair M. S.; Swanson, Mark E.; Larson, Andrew J. (Ecological processes, 2020)
The reintroduction of fire to landscapes where it was once common is considered a priority to restore historical forest dynamics, including reducing tree density and decreasing levels of woody biomass on the forest floor. However, reintroducing fire causes tree mortality that can have unintended ecological outcomes related to woody biomass, with potential impacts to fuel accumulation, carbon sequestration, subsequent fire severity, and forest management. In this study, we examine the interplay between fire and carbon dynamics by asking how reintroduced fire impacts fuel accumulation, carbon sequestration, and subsequent fire severity potential. Beginning pre-fire, and continuing 6 years post-fire, we tracked all live, dead, and fallen trees ≥ 1 cm in diameter and mapped all pieces of deadwood (downed woody debris) originating from tree boles ≥ 10 cm diameter and ≥ 1 m in length in 25.6 ha of an Abies concolor / Pinus lambertiana forest in the central Sierra Nevada, California, USA. We also tracked surface fuels along 2240 m of planar transects pre-fire, immediately post-fire, and 6 years post-fire. Six years after moderate-severity fire, deadwood ≥ 10 cm diameter was 73 Mg ha −1 , comprised of 32 Mg ha −1 that persisted through fire and 41 Mg ha −1 of newly fallen wood (compared to 72 Mg ha −1 pre-fire). Woody surface fuel loading was spatially heterogeneous, with mass varying almost four orders of magnitude at the scale of 20 m × 20 m quadrats (minimum, 0.1 Mg ha −1 ; mean, 73 Mg ha −1 ; maximum, 497 Mg ha −1 ). Wood from large-diameter trees (≥ 60 cm diameter) comprised 57% of surface fuel in 2019, but was 75% of snag biomass, indicating high contributions to current and future fuel loading. Reintroduction of fire does not consume all large-diameter fuel and generates high levels of surface fuels ≥ 10 cm diameter within 6 years. Repeated fires are needed to reduce surface fuel loading.